When should we stop mammography screening for breast cancer in elderly women?. Issue 2 (February 2017) - Putzer, Darryl; Frueh, Janice
Abstract : EVIDENCE‐BASED ANSWER : The answer is unclear. Mammography screening provides no mortality benefit for women aged 70 to 74 years (SOR: A, systematic reviews of 2 RCTs). However, mammography screening is recommended every 2 years by the US Preventive Services Task Force (USPSTF) and every 2 to 3 years by the Canadian Task Force on Preventive Health Care (CTFPHC) for women aged 70 to 74. Neither guideline provides a recommendation for women older than 74 years (SOR: C, consensus guidelines).